Acetyl-L-carnitine ameliorates atherosclerosis in LDLR−/− mice by modulating cholesterol metabolism through SREBP2-dependent cholesterol biosynthesis - Xing, Jingci; Du, Zhiyong; Li, Fan; Wang, Yu; Zhang, Zihan; Gao, Xiaoqian; Han, Lijie; Sun, Xuechun; Sun, Haili; Du, Yunhui; Hu, Chaowei; Yu, Huahui; et al. (Frontiers in Nutrition, 2024)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) is the leading cause of mortality globally. Hypercholesterolemia accelerates atherosclerotic development and is an independent modifiable risk factor for ASCVD. Reducing cholesterol levels is effective in preventing ASCVD. Acetyl-L-carnitine (ALC) is an endogenous molecule that plays a primary role in energy metabolism; however, its effect on cholesterol metabolism remains unclear.MethodsWe collected plasma samples and clinical data from 494 individuals with hyperlipidemia. Targeted metabolomics were used to measure plasma ALC levels and explore the association of ALC with clinical cholesterol levels. Additionally, we explored the effects of ALC in cholesterol levels and cholesterol metabolism in a murine hypercholesterolemia model. An LDLR−/− mouse-based atherosclerotic model was established to investigate the roles of ALC on atherosclerotic progression.ResultsPlasma ALC concentrations were significantly negatively correlated with plasma total cholesterol (TC) levels (r = −0.43, p < 0.0001) and low-density lipoprotein cholesterol (LDL-C; r = −0.53, p < 0.0001). Incorporating ALC into the diet significantly reduced plasma TC and LDL-C levels, downregulated genes involved in cholesterol synthesis, such as sterol regulatory element-binding protein 2 (SREBP2) and 3-hydroxy-3-methyl-glutaryl-CoA reductase, and upregulated low-density lipoprotein receptor expression. ALC supplementation substantially lowered plasma TC levels and inhibited atherosclerosis in LDLR−/− mice.ConclusionALC reduced atherosclerotic plaque formation by lowering plasma cholesterol levels via suppression of SREBP2-mediated cholesterol synthesis, thus suggesting that ALC is a potential therapeutic target for ASCVD.